Plagiarisme dalam Pendidikan Magister di Indonesia: Ancaman bagi Kualitas dan Reputasi Akademik - Argo, Henrikus Jatining Wahyu; Heridadi Heridadi; Sovian Aritonang; Pujo Widodo; Kusuma Kusuma; Wilopo Wilopo (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines the issue of plagiarism within Indonesia's graduate education system, highlighting its impact on academic integrity and the overall quality of education. Plagiarism, defined as the use of others' work without proper attribution, is increasingly common due to advances in technology and widespread access to information. This paper investigates the factors contributing to plagiarism among graduate students, including individual motivations, lack of understanding about proper citation, and external pressures such as lenient institutional policies and limited supervision. The study uses a qualitative literature review, incorporating findings from recent academic research and relevant legal regulations, to analyze these contributing factors and propose strategies for improvement. Key recommendations include strengthening institutional policies, providing comprehensive training on citation practices, and integrating anti-plagiarism software to ensure academic honesty. The findings underscore the need for a sustained commitment to fostering a culture of integrity and originality within Indonesian graduate programs. By addressing these issues, educational institutions can enhance student competence and maintain the credibility of Indonesian higher education in an increasingly globalized academic environment.